Chiral Anthranyl Trifluoromethyl Alcohols: Structures, Oxidative Dearomatization and Chiroptical Properties. Issue 72 (31st October 2022) - Sonet, Dorian; Cayla, Mattéo; Méreau, Raphaël; Morvan, Estelle; Lacoudre, Aline; Vanthuyne, Nicolas; Albalat, Muriel; Bassani, Dario M.; Scalabre, Antoine; Pouget, Emilie; Bibal, Brigitte
Abstract: Chiral trifluoromethyl alcohol groups were introduced at the hindered ortho positions of 9, 10‐diphenylanthracenes to investigate their effects on the physical properties and reactivity towards oxidative dearomatization. In such compact structures, the position in different quadrants and the preferred orientation of the −CH(OH)CF3 groups were determined by the relative and absolute configurations of each stereoisomer, respectively. As a consequence, the stereochemistry governs the organization of the H‐bonded molecules in single crystals (homochiral dimers vs ribbon), whereas in chlorinated solvents, they all behave as discrete compounds. Concerning their reactivity, the stereospecific dearomative oxidation of these molecules leads to 9, 10‐bis‐spiro‐isobenzofuran‐anthracenes, when using organic single‐electron transfer oxidants. The chiroptical properties of the alcohols and the corresponding dearomatized products were compared and showed an important modulation of the intensity. Abstract : Chiral diphenylanthracenes with two fluorinated alcohols have two stereogenic centers and syn / anti atropisomery. Consequently, depending on their stereochemistry, they make different Hydrogen‐bonded self‐assemblies in the solid state, whereas in solution, they specifically react to provide different chiral dearomatized bisfluorinated ethers. The chiroptical properties of all anthranyl fluorinated molecules have been compared.